Mitochondrial DNA Haplogroup Analysis Reveals no Association between the Common Genetic Lineages and Prostate Cancer in the Korean Population - Kim, Wook (Public Library of Science, 2008)
Mitochondrial DNA (mtDNA) variation has recently been suggested to have an association with various cancers, including prostate cancer risk, in human populations. Since mtDNA is haploid and lacks recombination, specific mutations in the mtDNA genome associated with human diseases arise and remain in particular genetic backgrounds referred to as haplogroups. To assess the possible contribution of mtDNA haplogroup-specific mutations to the occurrence of prostate cancer, we have therefore performed a population-based study of a prostate cancer cases and corresponding controls from the Korean population. No statistically significant difference in the distribution of mtDNA haplogroup frequencies was observed between the case and control groups of Koreans. Thus, our data imply that specific mtDNA mutations/lineages did not appear to have a significant effect on a predisposition to prostate cancer in the Korean population, although larger sample sizes are necessary to validate our results.